Life and Work on Sable Island: The Early Federal Record of Island Operations - Lane Jonah, Anne (Journal of the Royal Nova Scotia Historical Society, 2025)
Sable Island, Nova Scotia, approximately 300 kilometres east-southeast of Halifax on the edge of the North American continental shelf, has been known throughout the Atlantic world as a hazard to ships—its shores and surrounding shoals studded with the bones of approximately 350 wrecks. In 1801, a lifesaving service, the Humane Establishment, was put in place there under the responsibility of the British colony of Nova Scotia to aid ships in distress and those stranded on the island. With the British North America Act, the new government of Canada took responsibility for Sable Island and its small resident population of workers and their families scattered along the roughly forty-five-kilometre-long and one-kilometre-wide sand spit. This change would affect both life and work on the island as federal politicians and departments took over the operations, and more change would come as technology was introduced. This research report, drawn from a study of the federal record of Sable Island held at Library and Archives Canada, dating from the time of Confederation to the 1960s, provides insight into the evolution of services on the island, the changing public perceptions of the place and its importance, and how these two things shaped people’s lives and work. These records, found in a range of departmental fonds based on what service had administrative responsibility for the island at a given time, document administrative struggles, labour disputes, and moments of tragedy; they illuminate complex relationships—with families and the community, co-workers and bosses all intertwined. The records of individuals who lived and worked on the island and who managed the staff there reflect how the social, political, and technological world around the island changed both the context of work and the experiences and expectations of the people working there. Whereas each subject evoked in these records warrants a more in-depth study, the narrative created by this record merits sharing.